HUBUNGAN TINGKAT PENGETAHUAN DENGAN PERILAKU PENCEGAHAN SKABIES PADA MAHASISWA DI ASRAMA STIKES SANTA ELISABETH MEDAN TAHUN 2023 - Lili Suryani Tumanggor; Lilis Novitarum; Intan Maria Margaretha Sitanggang (Bajang Institute, 2023)
Scabies is a skin disease caused by the mite Sarcoptes scabiei and is a global skin health problem. The hostel is one of the high- risk places to experience scabies, so it needs more attention to prevent scabies. One of the internal factors that support the formation of scabies prevention behavior is the level of knowledge. The purpose of this study is to find out the relationship between knowledge and scabies prevention behavior in dormitory students at the STIKes Santa Elisabeth Medan 2023. The method used is descriptive correlational with a cross sectional approach. The sampling technique in this study is stratified random sampling obtained by 221 respondents. The results show that the majority of students had good knowledge of 215 people (97.3%) and the majority of students have good behavior, namely 210 people (95%). Based on the results of the Fisher's Exact statistical test, it is obtained a p- value = 1.000 (p>0.05), so there is no significant relationship between the level of knowledge and scabies prevention behavior in sormitory students at the STIKes Santa Elisabeth Medan. It is hoped that students will maintain behavior in maintaining personal and environmental hygiene in order to avoid skin health problems, one of which is scabies.